2019
DOI: 10.1177/1071100719895268
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Correction of the Modified Lapidus Procedure With a First Metatarsal to Intermediate Cuneiform Cross-Screw Technique

Abstract: Background: Recurrence of deformity remains a concern when fusing the first tarsometatarsal joint for correction of hallux valgus (HV). A recently described construct adds an additional point of fixation from the plantar medial first metatarsal to the intermediate cuneiform. The purpose of this study was to determine the maintenance of correction of the first and second intermetatarsal angle, hallux valgus angle, and tibial sesamoid position after undergoing a first tarsometatarsal joint arthrodesis using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…Subsequently, reliable and reproducible 2D measures of HV severity such as the hallux valgus angle and intermetatarsal angle were developed and are still used ubiquitously today. 2,16,17,21,27,36,46 Further, numerous operations to normalize these quantitative measures of HV deformity also exist. 9,16,46 Despite the use of these 2D quantitative measures and operative correction of sagittal and transverse plane deformities, consistent rates of poor outcomes and HV recurrence persist with operative correction.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, reliable and reproducible 2D measures of HV severity such as the hallux valgus angle and intermetatarsal angle were developed and are still used ubiquitously today. 2,16,17,21,27,36,46 Further, numerous operations to normalize these quantitative measures of HV deformity also exist. 9,16,46 Despite the use of these 2D quantitative measures and operative correction of sagittal and transverse plane deformities, consistent rates of poor outcomes and HV recurrence persist with operative correction.…”
Section: Introductionmentioning
confidence: 99%
“…Langan et al also included an intercuneiform fusion in order to improve foot stability. There was a significant reduction in the preoperative and postoperative IMA and HVA measurements, without a significant change postoperatively in cases of joint fusion [17]. Their study helps to validate the stability of the construct used by the senior author.…”
Section: Discussionmentioning
confidence: 80%
“…Possible benefits of this intercuneiform screw have conflicting support in the current literature. The intercuneiform screw has support from the aforementioned studies, which demonstrated the value of the additional construct stability more proximally [15][16][17]. However, a screw in this area has been studied biomechanically by Feilmeier et al [26] and does not increase stability of the first ray in the transverse or coronal planes in a TMT arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations